Analysis of Tourism Suitability and Carrying Capacity of Mangrove Areas in Sumberkima Village, Buleleng Regency, Bali - Muhammad Fikri Deliansyah; Dwi Budi Wiyanto; Gede Surya Indrawan (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2025)
The mangrove forests in Sumberkima Village, Buleleng Regency, Bali, hold significant potential for development as eco-friendly tourism destinations. This study aims to analyze the mangrove health index and the suitability of the mangrove area as an ecotourism destination, and to determine the area's carrying capacity for tourism activities. The methodology involves analyzing ecotourism parameters, including mangrove thickness and density, mangrove species, tidal patterns, and the presence of biotic objects. Primary data were collected through field observations, while secondary data were obtained from official sources. The study results indicate that the mangrove area in Sumberkima Village has a mangrove health index ranging from 34.89% to 51.18%, categorized as moderate. The mangrove tourism suitability index reveals that one observation station falls into the